2020
DOI: 10.1007/s40544-020-0439-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of titanium carbide and alumina on the friction increment for Cu-based metallic brake pads under different initial braking speeds

Abstract: To understand the effect of abrasives on increasing friction in Cu-based metallic pads under different braking speeds, pad materials with two typical abrasives, titanium carbide (TiC) and alumina (Al2O3), were produced and tested using a scale dynamometer under various initial braking speeds (IBS). The results showed that at IBS lower than 250 km/h, both TiC and Al2O3 particles acted as hard points and exhibited similar friction-increasing behavior, where the increase in friction was not only enhanced as IBS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Referring to existing studies, it is found that the simulation experiment under low load and sliding speed will not result in changes in the friction and wear mechanism of materials (Peng et al , 2021; Zuo et al , 2022). In this experiment, the friction radius is 15 mm, the contact stress is 1.0 MPa and the loading speed is 0.3 m/s.…”
Section: Methodsmentioning
confidence: 87%
“…Referring to existing studies, it is found that the simulation experiment under low load and sliding speed will not result in changes in the friction and wear mechanism of materials (Peng et al , 2021; Zuo et al , 2022). In this experiment, the friction radius is 15 mm, the contact stress is 1.0 MPa and the loading speed is 0.3 m/s.…”
Section: Methodsmentioning
confidence: 87%
“…Consequently, the hardness is enhanced [46,47]. For the compression test, the presence of the nano-ceramic particles dispersed formally in the Cu matrix prevents the dislocation of the particles.…”
Section: Discussionmentioning
confidence: 99%
“…This is a signal of increasing material strength with decreasing ductility. This may be attributed to the good adhesion between Cu matrix and TiC nanoparticles than between Cu and Al2O3 [46]. An extreme drop in the Cu-Al2O3 composite strength is noticed at 9 wt.% of Al2O3.…”
Section: Strengthening Criteriamentioning
confidence: 94%
“…Uyyuru et al [26] studied that sliding speed proportionally influences the tribolayer thickness. Research by Peng et al [27] on the influence of the Cu/Fe ratio and found that with an increase in Fe content stable tribo-oxides layers were formed which retards its destruction. Cu-based composites with 14 wt%Fe improved the hardness from 9.21 to 20.39HBW [28].…”
Section: Introductionmentioning
confidence: 99%